Results of second trimester prenatal diagnosis of cystic fibrosis in risk families - Vávrová, V; Thomásová, H; Macek, M (Czechoslovak medicine, 1989)
Investigation of 17 children delivered after prenatal examination of amniotic fluid GGT was performed. GGT testing was carried out in the 17th-18th week of gestation. The development of children unaffected by cystic fibrosis was predicted. In all pregnancies, clinically healthy children with normal sweat chloride concentrations were delivered. Our results confirm the advantage of the examination of microvillar enzymes in amniotic fluid in the second trimester as a rather reliable method of fetal diagnosis of cystic fibrosis if it is impossible to use the molecular genetic methods in the first trimester.
Keywords: gama-glutamyltransferasa; Infant; Humans; Pregnancy; Pregnancy Trimester, Second; kojenec; Chlorides; chloridy; Prenatal Diagnosis; Female; rizikové faktory; dospělí; gamma-Glutamyltransferase; lidé; Amniotic Fluid; druhý trimestr těhotenství; Adult; Cystic Fibrosis; Sweat; ženské pohlaví; Male; plodová voda; prenatální diagnóza; těhotenství; cystická fibróza; Clinical Enzyme Tests; mužské pohlaví; pot; Risk Factors; klinické enzymatické testy